Literacy for the 21st century : a balanced approach - Tompkins, Gail E. (Upper Saddle River, NJ : Pearson Education/Merrill/Prentice Hall, 2010)
A comprehensive and thoroughly applied text that covers the information new and experienced teachers need to know to teach literacy effectively in Australian classrooms. It includes specific strategies to use in the classroom to develop successful readers and writers. Australian authors.
Includes bibliographical references and index.
Keywords: Language arts (Elementary).; Literature -- Study and teaching (Elementary).; Reading (Elementary).